Jenis Jenis Konflik Dalam Organisasi - Abdul Fiqrial Akbar; Gita Iranie Fatimatus Sholehah; Siti Komariah; Is’af Qushoyina Tsuraya; Mu’allimin Muallimin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Organizational conflict is an unavoidable dynamic that significantly affects effectiveness and productivity. This study examines various types of conflicts in organizations, such as interpersonal, intrapersonal, and structural conflicts, along with their impact on organizational performance. Through a literature review approach, this research explores conflict causes, including value differences, poor communication, and resource competition. The findings reveal that conflicts can yield positive outcomes, such as fostering innovation and strengthening relationships, while also leading to negative effects, such as stress and reduced performance. This study provides insights for organizational managers to constructively manage conflicts, ensuring organizational sustainability.